La dimension interreligieuse des droits internes des religions. L'expérience strabourgeoise - Messner, Francis (Daimon, 2017)
The interreUgious dimension of religious legal systems. The Strasbourg experience This article is focused on the contribution that a careful comparison of the elements shared by different religious legal systems can offer in terms of social consensus, living and working together, religious/eace. This analysis is required by the contemporary, sodoreligious reality, that marks the en of the existence of homogeneous religious groups: the institutionalization of religious pluralism, the individualisation of religious beliefs, the religious radicalization of certain movements and the weakening of the power of religious authorities over the members of their communities make a reflection on the interreligious dimension of the religious laws an indispensable tool to understand what is going on in France and other European countries